COUNSELLING FOR 21ST CENTURY POLITICAL CHANGES IN ACHIEVING NIGERIA’S VISION 20:2020 - M.B.I, Omoniyi (European Scientific Journal, ESJ, 2012)
Comparatively, the rate at which men participate in politics is incredibly higher than their female counterparts. Though there has been a progressive increase in the trend of women participation in politics, it has been more in the areas of appointments and not elections. The participation is considered very low considering the international standard of 30% benchmark. The major thrust of this paper is to bring into focus the existing level of political participation of Nigeria women. The place of women in the different political dispensations was highlighted. Thereafter, counselling for political change in attitudes and pre-dispositions were made towards achieving better participation of women in politics to achieve the Nation’s vision 20:2020.